Silane modified polyether prepared from ethoxyquin polymer as well as preparation method and application of silane modified polyether
By amine decomposition and polymerization of ethoxyquinoline polymer and propylene oxide, combined with chemical modification of acid anhydride and epoxy organosiloxane, silane modified polyether was prepared, which solved the problem of resource utilization of heavy component polymers of ethoxyquinoline distillation, and achieved the preparation of high-performance silane modified polyether.
Patent Information
- Application Number
- CN202510006244.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-09-27
- Filing Date
- 2025-01-03
- Publication Date
- 2025-04-11
AI Technical Summary
The prior art is difficult to effectively utilize ethoxyquinoline to distillate the recombinant polymer, resulting in waste of resources.
The amine-decomposition reaction of ethoxyquinoline polymer and propylene oxide is prepared, and polymerized with propylene oxide as a starting agent to obtain ethoxyquinoline polyether polyol, which is then chemically modified with acid anhydride and epoxy organosiloxane to prepare silane-modified polyether.
The resource utilization of the heavy component polymer of ethoxyquinoline distillation is realized. The silane modified polyether prepared has the advantages of high strength, strong adhesion, moisture resistance, low odor and environmental protection, and is suitable for the preparation of glass glue, sealant, nail-free glue, ceramic tile adhesive, etc.
Smart Images

Figure BDA0005226952010000032 
Figure BDA0005226952010000041 
Figure BDA0005226952010000051
Abstract
Description
Technical Field
[0001] The invention belongs to the field of materials and relates to a silane-modified polyether prepared by using ethoxyquinoline polymer and a preparation method and application thereof. Background Art
[0002] Ethoxyquinoline is a very economical and effective antioxidant, which is widely used. It is not only used for food preservation, but also can slow down rubber aging, inhibit vitamin oxidation, and prevent fruit skin from discoloration due to oxidation. However, for every ton of ethoxyquinoline crude oil produced, about 0.25 tons of distilled heavy polymers will be produced. The resource utilization of heavy polymers has always been a technical problem that has plagued the development of the industry.
[0003] Polymers with ether bonds (—R—O—R—) in the main chain of polymer molecules and more than 2 hydroxyl groups (—OH) in their end or side groups are collectively referred to as polyether polyols. They are colorless to brown viscous liquids at room temperature, usually soluble in aromatic hydrocarbons, halogenated hydrocarbons, alcohols, ketones, and hygroscopic. Polyether polyols are synthesized by homopolymerization or copolymerization of polyhydroxy or polyamine compounds as initiators with oxidized olefins in the presence of catalysts. Polyether polyols are commonly used in the manufacture of general-purpose polyurethane foams, adhesives, elastomers, etc., and are widely used. Special polyether polyols are also used as defoamers, surfactants, etc.
[0004] Silane-modified polyether, referred to as MS-Polymer (MS polymer), the adhesive made of it can also be called MS glue, modified silicone glue, silicone-modified polyether glue. It was first developed by Japan's Kaneka Chemical. Usually, it is made by grafting silane compounds containing hydrolyzable siloxane groups to the two ends of a polyether with difunctionality through a specific chemical reaction. The main chain of the silane-modified polyether is a macromolecular polyether structure, which brings good flexibility, impact resistance, deformation and displacement resistance, ductility and hydrolysis resistance to the base polymer. The two ends of the silane-modified polyether contain ≥2 hydrolyzable siloxane groups. After contact with air, they are hydrolyzed and condensed to form Si-O-Si bonds, giving the silane-terminated polyether excellent water resistance, weather resistance, aging resistance and other properties. It can be seen that silane-modified polyether has the advantages of both silicone and flexible polyether, and has excellent comprehensive performance. Therefore, silane-modified polyether is widely used. Today, the adhesive industry is facing conflicting demands, hoping that raw materials can meet strict environmental regulations while maintaining their high performance. Therefore, the research and development of silane-modified polyethers is increasingly valued by technicians.
[0005] Since silane-modified polyethers have excellent properties, if the application technology of silane-modified polyethers can be combined with the heavy components of ethoxyquinoline distillation to achieve the resource utilization of the heavy components of ethoxyquinoline distillation polymers, then the technical problems that have been plaguing the development of the industry will find a feasible solution. Summary of the invention
[0006] The object of the present invention is to provide a silane-modified polyether prepared from ethoxyquinoline polymer in view of the above-mentioned deficiencies in the prior art.
[0007] The purpose of the present invention can be achieved through the following technical solutions:
[0008] A silane-modified polyether prepared from an ethoxyquinoline polymer is prepared by the following method: an ethoxyquinoline polymer is subjected to an aminolysis reaction with propylene oxide to prepare an amino alcohol; the amino alcohol is then used as an initiator to undergo a polymerization reaction with propylene oxide to prepare an ethoxyquinoline polyether polyol; and the ethoxyquinoline polyether polyol is chemically modified with an acid anhydride and an epoxy organic siloxane to prepare a silane-modified polyether.
[0009] Preferably, the silane-modified polyether prepared from the ethoxyquinoline polymer is prepared by the following method: using butyl acetate or xylene as a reaction solvent, under the action of a catalyst, the ethoxyquinoline polymer and propylene oxide undergo an aminolysis reaction to prepare an amino alcohol; using butyl acetate or xylene as a reaction solvent and the amino alcohol as an initiator, under the action of a catalyst, the amino alcohol and propylene oxide undergo a polymerization reaction to prepare an ethoxyquinoline polyether polyol; under the action of a catalyst, the ethoxyquinoline polyether polyol is chemically modified with anhydride and epoxy organic siloxane to prepare a silane-modified polyether.
[0010] The ethoxyquinoline polymer is prepared by taking the ethoxyquinoline distillation kettle residue as raw material through the following method: mixing the ethoxyquinoline distillation kettle residue with an organic solvent selected from butyl acetate or xylene, stirring and heating to 50-100° C., dissolving at a temperature of 50-100° C. for 1-3 hours, cooling after uniform dissolution, filtering, and obtaining an ethoxyquinoline polymer solution.
[0011] Preferably, the ethoxyquinoline polymer is prepared by the following method: adding the ethoxyquinoline distillation kettle residue and an organic solvent selected from butyl acetate or xylene into a dissolution kettle, stirring and heating to 60-90° C., dissolving at a temperature of 60-90° C. for 1-2 hours, cooling after uniform dissolution, filtering, and obtaining an ethoxyquinoline polymer solution.
[0012] The xylene can be various isomers of xylene, and the most commonly used is industrial grade mixed xylene.
[0013] Preferably, the mixture is cooled to 40°C and filtered.
[0014] The filtration adopts filter paper with a pore size of 20 microns.
[0015] Ethoxyquinoline is generally prepared by condensing p-aminophenyl ether with acetone under the action of p-toluenesulfonic acid as a catalyst, using toluene as a reaction solvent. After the reaction is completed, a Na2CO3 aqueous solution with a concentration of about 0.1 g / mL is added to stand for stratification, and the upper organic layer is taken. The organic layer enters a distillation kettle for distillation, and toluene, a fraction 1 with an ethoxyquinoline content of less than 78%, a fraction 2 with an ethoxyquinoline content of 78% or less and less than 88% (the distillation temperature is 190±5°C and the vacuum degree is -0.096MPa±0.001MPa), and a finished product with an ethoxyquinoline content of 88% or less (the distillation temperature is 190±5°C and the vacuum degree is -0.096MPa±0.001MPa) are distilled out in sequence, and the ethoxyquinoline distillation kettle residue is obtained in a distillation tower.
[0016] Another object of the present invention is to provide a method for preparing a silane-modified polyether prepared from the ethoxyquinoline polymer, comprising:
[0017] Step (1), pretreatment of ethoxyquinoline still residue: mixing an organic solvent selected from butyl acetate or xylene with the ethoxyquinoline still residue, stirring and heating to 50-100° C., dissolving at 50-100° C. for 1-3 hours, cooling after uniform dissolution, filtering, filtering out black solid particles formed by high-temperature carbonization of organic matter, and obtaining an ethoxyquinoline polymer solution;
[0018] Step (2), using one selected from butyl acetate or xylene as a reaction solvent, in the presence of a catalyst, the ethoxyquinoline polymer and propylene oxide undergo an aminolysis reaction to prepare an amino alcohol;
[0019] Step (3), using one selected from butyl acetate or xylene as a reaction solvent and the amino alcohol prepared in step (2) as an initiator, in the presence of a catalyst, the amino alcohol and propylene oxide undergo a polymerization reaction to prepare an ethoxyquinoline polyether polyol;
[0020] Step (4), under the action of a catalyst, ethoxyquinoline polyether polyol is chemically modified with anhydride and epoxy organic siloxane to prepare a silane-modified polyether.
[0021] In step (1), the mass ratio of the butyl acetate or xylene to the ethoxyquinoline distillation kettle residue is 1:0.5 to 1:2.0, preferably 1:1.0 to 1:1.6.
[0022] The theoretical amine value of ethoxyquinoline is 258 mgKOH / g.
[0023] The amine value of the ethoxyquinoline polymer solution is usually 80 to 110 mgKOH / g.
[0024] In step (2), represents ethoxyquinoline polymer, ethoxyquinoline polymer and propylene oxide undergo aminolysis reaction to obtain an amino alcohol with a structure as shown in formula I, and the synthesis route is as follows:
[0025]
[0026] The mass ratio of the ethoxyquinoline polymer solution to propylene oxide (56.1×1000 / Av): [58.08×(1.0~1.1)]; wherein 56.1 is the relative molecular weight of KOH, Av is the amine value measured by the ethoxyquinoline polymer solution, and 58.08 is the relative molecular weight of propylene oxide.
[0027] The catalyst is one or two or more of trifluoromethanesulfonates such as lanthanum trifluoromethanesulfonate, neodymium trifluoromethanesulfonate, erbium trifluoromethanesulfonate, ytterbium trifluoromethanesulfonate, scandium trifluoromethanesulfonate, cerium trifluoromethanesulfonate, stannous trifluoromethanesulfonate, bismuth trifluoromethanesulfonate, etc., and the mixture is preferably one or two or more of lanthanum trifluoromethanesulfonate, ytterbium trifluoromethanesulfonate, and scandium trifluoromethanesulfonate.
[0028] The dosage of the catalyst is 0.1wt% to 1wt% of the total mass of the ethoxyquinoline polymer solution and propylene oxide.
[0029] The temperature of the aminolysis reaction is 80°C to 120°C, preferably 110°C to 120°C, the pressure of the aminolysis reaction is 0.1 to 0.4 MPa, and the end point of the aminolysis reaction is when the pressure of the reaction system drops to a constant level. Generally, the time of the aminolysis reaction is 1 to 8 hours, until the pressure in the kettle drops to a constant level.
[0030] Specifically, the amino alcohol is prepared by the following method: in a pressure reactor, in the presence of a catalyst, an ethoxyquinoline polymer solution and propylene oxide react at a temperature of 80°C to 120°C and a pressure of 0.1 to 0.4 MPa until the pressure in the reactor drops to a constant, and then cooled to below 50°C to obtain the amino alcohol.
[0031] Under the reaction conditions of the present invention, the epoxy group of propylene oxide is ring-opened and reacts with the secondary amine group of the ethoxyquinoline polymer to undergo addition reaction. When the pressure of the reaction system drops to a constant value, that is, the absorption of propylene oxide is completed, the reaction is considered to be finished.
[0032] In step (3), the amino alcohol with a structure as shown in formula I undergoes polymerization reaction with propylene oxide to obtain an ethoxyquinoline polyether polyol with a structure as shown in formula II. The synthesis route is as follows:
[0033]
[0034] The amount of the amino alcohol is calculated based on the ethoxyquinoline polymer solution in step (2), and the mass ratio of the ethoxyquinoline polymer solution to propylene oxide is (56.1×1000 / Av):[58.08×(1.0~50)], preferably (56.1×1000 / Av):[58.08×(3~40)], and more preferably (56.1×1000 / Av):[58.08×(3~6)]; wherein 56.1 is the molecular weight of KOH, Av is the amine value measured by the ethoxyquinoline polymer solution, and 58.08 is the relative molecular weight of propylene oxide. The amount of propylene oxide used in step (3) does not include the amount of propylene oxide used in step (2).
[0035] The catalyst is one of sodium formate, potassium formate, sodium benzoate and potassium benzoate or a mixture of two or more of them in any proportion; the amount of the catalyst is 1wt% to 5wt% of the total mass of the amino alcohol and propylene oxide.
[0036] The polymerization temperature is 100°C to 165°C, preferably 140°C to 155°C, the polymerization pressure is 0.1 to 0.6 MPa, preferably 0.1 to 0.4 MPa, and the polymerization time is 1 to 8 hours, preferably 3 to 7 hours. Generally, the end point of the polymerization reaction is when the pressure of the reaction system drops to a constant level.
[0037] After the reaction is completed, the organic solvent is removed by distillation under reduced pressure, activated clay is added for stirring, and then cyclic pressure filtration is performed until the solution becomes clear and transparent to obtain ethoxyquinoline polyether polyol.
[0038] The conditions for removing the organic solvent by reduced pressure distillation are: vacuum degree -0.098MPa, temperature 120°C.
[0039] Specifically, the ethoxyquinoline polyether polyol is prepared by the following method: in a pressure reactor, in the presence of a catalyst, amino alcohol and propylene oxide undergo polymerization reaction until the pressure in the reactor drops to a constant level, the temperature is lowered to 80° C., reduced pressure distillation is started to recover the organic solvent to 120° C., no organic solvent is distilled out for 10 minutes at a vacuum degree of -0.098 MPa and a temperature of 120° C., the distillation is terminated, the temperature is lowered to 60° C., activated clay is added and stirred for 30 minutes, and cyclic pressure filtration is performed until it is clear and transparent to obtain the ethoxyquinoline polyether polyol.
[0040] More specifically, the ethoxyquinoline polyether polyol is prepared by the following method: after the reaction in step (2) is completed, when the reaction liquid drops to ≤50°C, a catalyst is added, and then the temperature is raised to a set reaction temperature, and propylene oxide is continuously and slowly added dropwise to carry out a polymerization reaction until the pressure in the kettle drops to a constant level, the temperature is lowered to 80°C, and reduced pressure distillation is started to recover the organic solvent to 120°C. At a vacuum degree of -0.098MPa and a temperature of 120°C, no organic solvent is distilled out for 10 minutes, the distillation is terminated, the temperature is lowered to 60°C, activated clay is added and stirred for 30 minutes, and cyclic pressure filtration is carried out until it is clear and transparent to obtain the ethoxyquinoline polyether polyol.
[0041] In step (4), the mass ratio of the ethoxyquinoline polyether polyol to the acid anhydride is (56.1×1000 / V OH ):[(0.5~1.0)×M1]; The mass ratio of the ethoxyquinoline polyether polyol to the epoxy organic siloxane is (56.1×1000 / V OH ):[(0.5~1.0)×M2]; where 56.1 is the relative molecular weight of KOH, V OH M2 is the hydroxyl value measured for ethoxyquinoline polyether polyol. The hydroxyl value of ethoxyquinoline polyether polyol is measured according to the national standard “GB / T 12008.3-2009 Plastic polyether polyol Part 3: Determination of hydroxyl value”. M3 is the relative molecular weight of the acid anhydride, and M4 is the relative molecular weight of the epoxy organosiloxane.
[0042] The acid anhydride is succinic anhydride (CAS No: 108-30-5, relative molecular weight 100.07).
[0043] The epoxy organic siloxane is 3-glycidyloxypropylmethyldimethoxysilane (CAS No: 65799-47-5, relative molecular weight 220.34), 3-glycidyloxypropylmethyldiethoxysilane (CAS No: 2897-60-1, relative molecular weight 248.39), preferably 3-glycidyloxypropylmethyldimethoxysilane.
[0044] The catalyst is a Lewis base, a quaternary ammonium salt, a quaternary phosphonium salt, preferably triethylamine; the amount of the catalyst is 100-20000ppm, preferably 1000-10000ppm, of the total mass of ethoxyquinoline polyether polyol, acid anhydride and organosiloxane.
[0045] The temperature of the chemical modification is 60°C to 150°C, preferably 80°C to 125°C, and the time of the chemical modification is 1 to 9 hours.
[0046] Specifically, the silane-modified polyether is prepared by the following method: under the action of a catalyst, ethoxyquinoline polyether polyol is chemically modified with anhydride and epoxy organic siloxane to obtain the target product silane-modified polyether.
[0047] More specifically, the silane-modified polyether is prepared by the following method: anhydride, epoxy organic siloxane and catalyst are mixed, stirred and heated, ethoxyquinoline polyether polyol is added dropwise through a constant pressure dropping funnel, and after the addition is completed, the reaction is continued until the acid value of the system is ≤0.5 mgKOH / g, cooled, filtered, and the target product silane-modified polyether is obtained.
[0048] In the chemical modification process, the anhydride ring opens and undergoes an esterification reaction with the hydroxyl group of the ethoxyquinoline polyether polyol to form a carboxyl group, and the carboxyl group then undergoes a ring opening and esterification reaction with the epoxy group of the organosiloxane, which are all well-known chemical reactions.
[0049] Taking succinic anhydride as anhydride and 3-glycidyloxypropylmethyldimethoxysilane as an example, the synthesis route of silane-modified polyether is as follows:
[0050]
[0051]
[0052] Another object of the present invention is to provide the use of the silane-modified polyether prepared from the ethoxyquinoline polymer in the preparation of glass glue, sealant, nail-free glue, and tile adhesive.
[0053] Beneficial effects of the present invention:
[0054] Ethoxyquinoline distillation kettle residue is a chemical solid waste. The invention adopts organic solvent butyl acetate or xylene to dissolve the ethoxyquinoline distillation kettle residue, extracts organic molecules, filters and removes high-temperature carbides, then carries out aminolysis reaction of the secondary amine functional group of the ethoxyquinoline polymer with propylene oxide, introduces hydroxyl groups, further uses amino alcohol as an initiator, carries out polymerization reaction with propylene oxide under the action of a catalyst to prepare polyether polyol, and further reacts the polyether polyol with anhydride and epoxysiloxane to prepare the target product silane-modified polyether.
[0055] The silane groups in the silane-modified polyether prepared from the ethoxyquinoline polymer of the present invention are hydrolyzed to form silane-oxygen bonds (Si-O-Si) to achieve cross-linking and curing. At the same time, due to the introduction of the rigid nitrogen-containing heteroatom quinoline ring structure and the ester bond structure with high cohesive energy, the silane-modified polyether prepared from the ethoxyquinoline polymer of the present invention has the advantages of high strength, strong adhesion, moisture resistance, low odor, environmental protection, and solvent-free after curing. The silane-modified polyether can be used to prepare glass glue, sealant, nail-free glue, tile adhesive, etc., and can be widely used in the construction industry.
[0056] The invention realizes the resource utilization of ethoxyquinoline distillation kettle residue, thereby turning waste into treasure. DETAILED DESCRIPTION
[0057] Determination of amine value by perchloric acid-acetic acid titration [1] :
[0058] Weigh about 0.2g (accurate to 0.0001g) of sample, place it in a 250mL conical flask, add about 25mL of glacial acetic acid solution, stir magnetically to fully dissolve, add 2 to 3 drops of crystal violet indicator (dissolve 0.5g of crystal violet in 100mL of glacial acetic acid), and titrate with the prepared calibrated 0.1mol / L perchloric acid standard solution until the solution changes from purple to pure blue, which is the titration end point. Titrate in parallel two or three times and take the average value.
[0059] The calculation formula of amine value is:
[0060] Where:
[0061] C—concentration of perchloric acid standard solution, mol / L;
[0062] V—volume of perchloric acid standard solution consumed by the sample, mL;
[0063] m—mass of sample, g;
[0064] 56.1—The mass of potassium hydroxide per mole.
[0065] Example 1
[0066] The first step is to add 800 g of xylene and 800 g of ethoxyquinoline distillation kettle residue into a 2L dissolving kettle, stir and heat to 90° C., dissolve at 90° C. for 2 hours, and after uniform dissolution, cool to 40° C. and filter with filter paper with a pore size of 20 μm to filter out black solid particles formed by high-temperature carbonization of organic matter to obtain 1515 g of xylene solution of ethoxyquinoline polymer, and the amine value is 93.2 mgKOH / g as determined by perchloric acid-acetic acid titration.
[0067] In the second step, 1203.86 grams of the xylene solution of the ethoxyquinoline polymer obtained in the first step and 4 grams of lanthanum trifluoromethanesulfonate (CAS No. 52093-26-2) were added to a 5L pressure reactor, stirring was started, the temperature was raised to 110°C, and 127 grams of propylene oxide was added dropwise for reaction. During the addition, the temperature was controlled at 110°C to 120°C and the pressure was controlled at 0.10 to 0.40 MPa. The addition was completed within 2 hours. After the addition was completed, the reaction was carried out at 110°C to 120°C for 2 hours. At this time, the pressure in the reactor dropped to a constant level, and the reactor was cooled to below 50°C to obtain amino alcohol. No separation or purification was required, and the next step of reaction was directly carried out.
[0068] The third step is to drop 20 grams of sodium formate into a 5L pressure reactor, start stirring, heat to 150°C, start dripping 696.96 grams of propylene oxide to react, control the temperature at 150°C to 155°C and the pressure at 0.10 to 0.40MPa during the dripping process, and complete the dropwise addition within 4 hours. After completion of the dropwise addition, the reaction is carried out at 150°C to 155°C for 3 hours, at which time the pressure in the reactor drops to a constant level, cool to 80°C, start underpressure distillation to recover xylene to 120°C, and at a vacuum degree of -0.098MPa and a temperature of 120°C, continue to distill without xylene for 10 minutes, terminate distillation, cool to 60°C, add 20 grams of activated clay and stir for 30 minutes, then perform a circulating filter press until clear and transparent to obtain 1398 grams of ethoxyquinoline polyether polyols and recover 590 grams of xylene.
[0069] The designed hydroxyl equivalent (the mass number of a compound containing 1 mol of hydroxyl group) of ethoxyquinoline polyether polyol is 712.76 g / mol, and the measured hydroxyl equivalent is 713.22 g / mol; wherein, the conversion relationship between the hydroxyl equivalent and the hydroxyl value is: hydroxyl equivalent = 56.1 × 1000 / hydroxyl value; the hydroxyl value is measured in accordance with the national standard "GB / T 12008.3-2009 Plastic polyether polyols Part 3: Determination of hydroxyl value".
[0070] The fourth step is the preparation of silane-modified polyether: the preparation reaction is carried out under the condition of heating by a thermostatic electric heater. 98 grams of succinic anhydride, 218 grams of 3-glycidyloxypropylmethyldimethoxysilane and 3.1 grams of triethylamine are added to a four-necked flask, and the corresponding stirring device, heating device and temperature control device are connected. The temperature is stirred and heated to 80°C. 713.22 grams of the ethoxyquinoline polyether polyol prepared in the third step is added dropwise to the four-necked flask through a constant pressure dropping funnel. The temperature of the dropping process is controlled at 80-100°C, and the dropping is completed within 2 hours. After the dropping of the ethoxyquinoline polyether polyol is completed, the temperature is slowly raised to 120°C, and the reaction is kept at 120-125°C for 5 hours. When the acid value of the system is ≤0.5 mgKOH / g, it is cooled to 60°C and filtered through a 100-mesh gauze to obtain 1016.8 grams of silane-modified polyether (total feed amount is 1032.32 grams).
[0071] Example 2
[0072] raw material:
[0073] Silane-modified polyether: prepared as in Example 1;
[0074] Plasticizer: polypropylene glycol 2000 (DL2000, Jiangsu Litian Technology Co., Ltd. of Agenmon Group); dioctyl phthalate (DOP, Suzhou Jiading Chemical Technology Co., Ltd.);
[0075] Reinforcing filler: light calcium carbonate, commercially available;
[0076] Thixotropic agent: polyamide wax, commercially available;
[0077] Water absorbent: vinyl trimethoxysilane (A-171), Nanjing Xiangqian Chemical Co., Ltd.;
[0078] Coupling agent: γ-glycidyloxypropyltrimethoxysilane (CG-O187), γ-aminopropyltriethoxysilane (CG-A110), Shandong Sike New Materials Co., Ltd.
[0079] Stabilizer: 327, BASF, Germany;
[0080] Catalyst: Dibutyltin dilaurate, Sinopharm Group.
[0081] Preparation of silane modified polyether sealant:
[0082] Weigh the raw materials according to Table 1, and mix silane-modified polyether, light calcium carbonate (pre-dried), DL2000, DOP, polyamide wax, vinyl trimethoxysilane, 327 was added into a mechanical stirrer and stirred at 80 °C in vacuum for 2 h to evenly disperse the raw materials. The temperature was lowered to below 40 °C, and γ-glycidyloxypropyltrimethoxysilane, γ-aminopropyltriethoxysilane and dibutyltin dilaurate were added. The mixture was stirred for 0.5 h to obtain a silane-modified polyether sealant. The product was discharged and sealed.
[0083] Table 1: Ingredients of silane modified polyether sealant
[0084]
[0085] Comparative Example 1
[0086] A polyether polyol having the same hydroxyl equivalent as that in Example 1 was designed and prepared, using commonly used glycerol as an initiator and reacting with propylene oxide.
[0087] In a 3L pressure reactor, 92.09 g of glycerol (relative molecular weight 92.09) and 20 g of sodium formate were added, stirring was started, the temperature was raised to 150°C, and 2046.19 g of propylene oxide was added dropwise for reaction. During the addition, the temperature was controlled at 150°C to 155°C and the pressure was 0.10 to 0.40 MPa. The addition was completed within 4 hours. After the addition was completed, the temperature was kept at 150°C to 155°C for 3 hours until the pressure in the reactor dropped to a constant value, the temperature was lowered to 60°C, 10 g of activated clay was added, and stirring was carried out for 30 minutes. Circulation filter pressing was performed to obtain 2095 g of clear and transparent polyether polyol.
[0088] In this comparative example, the designed hydroxyl equivalent (the mass number of the compound containing 1 mol of hydroxyl group) of the polyether polyol is 712.76 g / mol, and the measured hydroxyl equivalent is 713.31 g / mol; wherein, the conversion relationship between the hydroxyl equivalent and the hydroxyl value is hydroxyl equivalent = 56.1 × 1000 / hydroxyl value; the hydroxyl value is measured according to the national standard "GB / T 12008.3-2009 Plastic polyether polyols Part 3: Determination of hydroxyl value".
[0089] Preparation of silane-modified polyether: The preparation reaction is carried out under the condition of heating by a thermostatic electric heater. 98 grams of succinic anhydride, 218 grams of 3-glycidyloxypropylmethyldimethoxysilane, and 3.1 grams of triethylamine are added to a four-necked flask, and the corresponding stirring device, heating device, and temperature control device are connected. The temperature is stirred and heated to 80°C. 713.31 grams of the polyether polyol prepared in the comparative example is added dropwise to the four-necked flask through a constant pressure dropping funnel. The temperature of the dropping process is controlled at 80-100°C, and the dropping is completed within 2 hours. After the polyether polyol is added dropwise, the temperature is slowly raised to 120°C, and the reaction is kept at 120-125°C for 5 hours. When the acid value of the system is ≤0.5 mgKOH / g, it is cooled to 60°C and filtered through a 100-mesh gauze to obtain 1016.9 grams of silane-modified polyether (total feed amount of 1032.41 grams).
[0090] Comparative Example 2
[0091] The silane-modified polyether prepared in Comparative Example 1 was used to replace the silane-modified polyether prepared in Example 1, and a sealant was prepared in the same manner as in Example 2, and the performance was tested.
[0092] The performance tests were performed on the sealants prepared in Example 2 and Comparative Example 2.
[0093] Instruments and equipment:
[0094] Shore A hardness tester, model HT-6510, Guangzhou Lantai Instrument Co., Ltd.; universal tensile machine, model LWK-520, Guangzhou Guangcai Testing Instrument Co., Ltd.
[0095] Performance test of silane modified polyether sealant:
[0096] (1) Determination of surface drying time
[0097] Under standard test conditions (temperature is 23±2℃, relative humidity is 50±5%, the same below), apply the sealant evenly on the glass plate, touch three different parts of the sealant surface with a glass rod every 1 minute until there is no sample adhering to the glass rod, and record the time when it does not stick to the glass rod.
[0098] (2) Determination of curing depth
[0099] Under standard test conditions, squeeze the sealant into a polyethylene cylindrical cup with an inner diameter of 40mm and a depth of about 40mm. Use a blade to trim the sealant surface so that the sealant is flush with the cylindrical cup. Curing for 24 hours, take out the cured layer in the cylindrical cup, and remove the uncured sealant. Use a thickness gauge to measure the film thickness and take the average value.
[0100] (3) Determination of Shore A hardness
[0101] Squeeze the sealant into the corresponding mold, try not to leave bubbles in the glue layer, scrape the surface flush with the edge of the mold, cure it under standard test conditions for 7 days, measure three parts with a Shore A hardness tester and take the average value.
[0102] (4) Tensile strength and elongation at break
[0103] Inject the sealant into the mold and use a scraper to flatten both sides. The thickness of the glue layer is 1.8-2.0mm. Curing under standard conditions for 10 days, take out the film and cut it into corresponding dumbbell-shaped test pieces. Use a universal tensile machine to test the tensile strength and elongation at break.
[0104] (5) Determination of bonding performance
[0105] Referring to GB / T 7124-2008 standard, an aluminum sheet with a length of 100 mm and a width of 25 mm was used as the substrate. Two substrates were taken, the substrate surfaces were polished with sandpaper, stains were wiped off with alcohol, and they were glued together with sealant to form a lap joint with a bonding area of 25 mm × 25 mm and a glue layer thickness of (1.6±0.1) mm.
[0106] ① Standard test conditions 1d tensile shear strength
[0107] The prepared overlap sheets were cured for 1 day under standard test conditions and tested on a material tensile machine according to the JC / T 2186-2013 standard of the building materials industry.
[0108] ② 7d tensile shear strength under standard test conditions
[0109] The prepared overlap sheets were cured for 7 days under standard test conditions and tested on a material tensile machine according to the JC / T 2186-2013 standard of the building materials industry.
[0110] Test results:
[0111] Table 2: Performance test results of silane modified polyether sealant
[0112] Sealant samples Example 2 Preparation Comparative Example 2 Preparation A commercially available product Surface drying time / min 35 39 36 Curing depth / mm / 24h 2.96 2.68 2.88 Shore A hardness / degree 57 45 51 Tensile strength / MPa 2.24 1.54 2.13 Elongation at break / % 357 323 348 1d tensile shear strength / MPa 1.57 1.53 1.55 7d tensile shear strength / MPa 3.54 2.96 3.42
[0113] The test results are shown in Table 2, which show that the silane-modified polyether sealant prepared in Example 2 has a 1d tensile shear strength of 1.57 MPa, which meets the standard requirement of 1.5 MPa, and a 7d tensile shear strength of 3.54 MPa, which exceeds the standard requirement of 2.5 MPa. The various properties are better than the silane-modified polyether sealant prepared in Comparative Example 2, and are not inferior to similar products on the market.
Claims
1. A silane-modified polyether prepared from an ethoxyquinoline polymer, characterized in that: The preparation method is as follows: an ethoxyquinoline polymer undergoes an aminolysis reaction with propylene oxide to prepare an amino alcohol; the amino alcohol is used as an initiator to undergo a polymerization reaction with propylene oxide to prepare an ethoxyquinoline polyether polyol; and the ethoxyquinoline polyether polyol is chemically modified with anhydride and epoxy organic siloxane to prepare a silane-modified polyether.
2. A method for preparing a silane-modified polyether prepared from the ethoxyquinoline polymer according to claim 1, characterized in that: include: Step (1), pretreatment of ethoxyquinoline still residue: mixing an organic solvent selected from butyl acetate or xylene with the ethoxyquinoline still residue, stirring and heating to 50-100° C., dissolving at 50-100° C. for 1-3 hours, cooling, filtering, and obtaining an ethoxyquinoline polymer solution; Step (2), using one selected from butyl acetate or xylene as a reaction solvent, in the presence of a catalyst, the ethoxyquinoline polymer and propylene oxide undergo an aminolysis reaction to prepare an amino alcohol; Step (3), using one selected from butyl acetate or xylene as a reaction solvent, in the presence of a catalyst, the amino alcohol and propylene oxide undergo a polymerization reaction to prepare an ethoxyquinoline polyether polyol; Step (4), under the action of a catalyst, ethoxyquinoline polyether polyol is chemically modified with anhydride and epoxy organic siloxane to prepare a silane-modified polyether.
3. The method for preparing a silane-modified polyether according to claim 2, wherein: In step (1), the mass ratio of the butyl acetate or xylene to the ethoxyquinoline distillation kettle residue is 1:0.5 to 1:2.0, preferably 1:1.0 to 1:1.
6.
4. The method for preparing a silane-modified polyether according to claim 2, wherein: In step (1), the amine value of the ethoxyquinoline polymer solution is 80-110 mgKOH / g.
5. The method for preparing a silane-modified polyether according to claim 2, wherein: In step (2), the mass ratio of the ethoxyquinoline polymer solution to propylene oxide is (56.1×1000 / Av):[58.08×(1.0-1.1)]; wherein Av is the amine value of the ethoxyquinoline polymer solution; The catalyst is at least one of lanthanum trifluoromethanesulfonate, neodymium trifluoromethanesulfonate, erbium trifluoromethanesulfonate, ytterbium trifluoromethanesulfonate, scandium trifluoromethanesulfonate, cerium trifluoromethanesulfonate, stannous trifluoromethanesulfonate, and bismuth trifluoromethanesulfonate, preferably at least one of lanthanum trifluoromethanesulfonate, ytterbium trifluoromethanesulfonate, and scandium trifluoromethanesulfonate; The dosage of the catalyst is 0.1wt% to 1wt% of the total mass of the ethoxyquinoline polymer solution and propylene oxide. The temperature of the aminolysis reaction is 80°C to 120°C, the pressure is 0.1 to 0.4 MPa, and the end point of the reaction is when the pressure of the reaction system drops to a constant level.
6. The method for preparing a silane-modified polyether according to claim 2, wherein: In step (3), the mass ratio of the ethoxyquinoline polymer solution to propylene oxide is (56.1×1000 / Av):[58.08×(1.0~50)], preferably (56.1×1000 / Av):[58.08×(3~40)], and more preferably (56.1×1000 / Av):[58.08×(3~6)]; wherein Av is the amine value of the ethoxyquinoline polymer solution; The catalyst is at least one of sodium formate, potassium formate, sodium benzoate and potassium benzoate; the amount of the catalyst is 1wt% to 5wt% of the total mass of the amino alcohol and propylene oxide; The polymerization reaction temperature is 100°C to 165°C, preferably 140°C to 155°C, the polymerization reaction pressure is 0.1 to 0.6 MPa, preferably 0.1 to 0.4 MPa, and the polymerization reaction time is 1 to 8 hours, preferably 3 to 7 hours.
7. The method for preparing a silane-modified polyether according to claim 2 or 6, characterized in that: In step (3), after the reaction is completed, the organic solvent is removed by distillation under reduced pressure, activated clay is added with stirring, and then cyclic pressure filtration is performed until the mixture becomes clear and transparent to obtain ethoxyquinoline polyether polyol.
8. The method for preparing a silane-modified polyether according to claim 2, wherein: In step (4), the mass ratio of the ethoxyquinoline polyether polyol to the acid anhydride is (56.1×1000 / V OH ):[(0.5~1.0)×M1]; The mass ratio of the ethoxyquinoline polyether polyol to the epoxy organic siloxane is (56.1×1000 / V OH ):[(0.5~1.0)×M2]; Among them, V OH is the hydroxyl value measured for ethoxyquinoline polyether polyol, M2 is the relative molecular weight of the anhydride, and M3 is the relative molecular weight of the epoxy organosiloxane.
9. The method for preparing a silane-modified polyether according to claim 2 or 8, characterized in that: In step (4), the acid anhydride is succinic anhydride; The epoxy organic siloxane is 3-glycidyloxypropylmethyldimethoxysilane or 3-glycidyloxypropylmethyldiethoxysilane, preferably 3-glycidyloxypropylmethyldimethoxysilane; The catalyst is a Lewis base, a quaternary ammonium salt, a quaternary phosphonium salt, preferably triethylamine; the amount of the catalyst is 100 to 20,000 ppm, preferably 1,000 to 10,000 ppm, of the total mass of the ethoxyquinoline polyether polyol, the acid anhydride and the organosiloxane; The temperature of the chemical modification is 60°C to 150°C, preferably 80°C to 125°C, and the time of the chemical modification is 1 to 9 hours.
10. Use of the silane-modified polyether prepared from the ethoxyquinoline polymer according to claim 1 in the preparation of glass glue, sealant, nail-free glue and tile adhesive.
Citation Information
Patent Citations
Tire
CA120386A
Cited By
High-performance silyl-terminated polyether sealant and preparation method thereof
CN122234744A